"Finding a safe space": A qualitative study of what makes help helpful for adolescents bereaved by suicide. Issue 10 (26th November 2022) - Andriessen, Karl; Krysinska, Karolina; Rickwood, Debra; Pirkis, Jane
Abstract: Experiencing a death by suicide is a devastating event in the lives of adolescents; however, little is known about what makes help helpful according to their experiences. Thematic analysis of individual and group interview data ( N  = 18) yielded four themes: feeling connected with, and understood by a helper, having a sense of control over, and access to the help as needed. Findings indicate that help should be based on supportive and educational approaches with respect to the adolescents' agency and the family context. Help must be accessible on a long-term basis while catering for flexible usage.